Mimetic Evil: A Conceptual and Ethical Study - Airaksinen, Timo (Problemos, 2020)
Irony and sarcasm are common linguistic tropes. They are both based on falsehoods that the speaker pretends to be true. I briefly characterize their differences. A third trope exists that works when the relevant propositions are true – yet its rhetorical effect resembles irony and sarcasm, I call it mocking. It is mimetic evil: an agent copies another so that the result ridicules him. The image is, in a limited way, true of him and it hurts; we all are vulnerable. I provide a systematic framework for understanding this phenomenon, mocking, in terms of emulation and simulation. Finally, I introduce an idea of universal mimesis and discuss René Girard’s theory of desire. He argues that desires are copies of a model. This may not be possible, and I suggest a modification to his theory. I pay attention to his idea of mimetic desire as a source of hatred, which is obviously related to what I call here mimetic mocking.
Keywords: Irony; Mocking; Emulation; Simulation; Girard